Human resource diversity and performance within the frame of organizations, teams and individuals - Senichev, Valery (Business: Theory and Practice, 2013)
The following paper provides a survey based on studies of relationships between Human Resource diversity and performance at different organisational levels. The importance of diversity in companies and society is becoming more and more important, therefore there is a need to identify circumstances and types of diversity, projects and teams, in which diversity can make an impact on company´s and working group success. The first part of the article is focused on the concept of diversity and Diversity Management in HR practices from the scientific and practical view. The second part is dedicated to the topic of performance and presents certain possibilities and indicators for performance measurement. The main report about the link between different types of diversity and performance at the organisational level, team level and the level of individuals will be produced in the third part. The findings from the studies show that diversity brings benefits and increases the performance in specific cases and under the certain circumstances. Moreover there is evidence that the positive effect of diversities is influenced or even caused by the presence of other factors.